DEAFinitely English Online materials for teachers of English as a Foreign Language for Deaf, deaf and hard of hearing students - Sedláčková, Jitka (Masaryk University Press, 2022)
The intention of this resource pack is to contribute to the language education of Deaf, deaf and hard of hearing (D/d/hh) students in post-secondary education. In general terms, the materials provide theoretical background for teaching languages ​​to D/d/hh students and their engagement in study stays abroad as well as practical booklets, which focus on the possibilities of teaching reading, writing and developing study skills in D/d/hh learners.